Technical Simulation Of The Process Of Reducing The Moisture Content Of Cotton Seeds And Its Analysis - M. Ibragimov; O. K. Matchanov; I. E. Tadjibekova; F. J. Isakova (International Scientific and Current Research Conferences, 2021)
To reduce the technical humidity of cotton seeds according to standard requirements, the method of electric contact heating was used. To reduce the moisture content of seeds under the influence of electric contact heating and convective ventilation in the chamber, a computer simulation model of heat and mass transfer processes in the seed layer was created. The simulation model was developed using the Simulink software.